HUBUNGAN KEBIASAAN SARAPAN, STATUS GIZI DAN TINGKAT PENDIDIKAN ORANG TUA DENGAN PRESTASI AKADEMIK SISWA - Al Muswah, Abdullah Ihsan; Suryaalamsah, Inne Indraaryani (JOURNAL HEALTH AND NUTRITIONS, 2024)
Academic achievement is a term used to show the results obtained by a person from the learning process in the world of education. Academic performance in Indonesia is still relatively low in the world. According to data from the World Best Countries For Education System in 2020, Indonesia ranks 70th with a quality index of 46.6 and an opportunity index of 42.97 out of 93 countries. The purpose of this study was to analyze the relationship between breakfast habits, nutritional status and education level of parents with academic achievement of MAN 2 students of Bogor Regency. The study was conducted in May 2023 at Madrasah Aliyah Negeri 2 Bogor Regency with a sample of 48 respondents taken by probability sampling.  This study used quantitative research methods with a cross sectional design. Data were collected using breakfast habit questionnaires for breakfast habits, Z-score for nutritional status and respondent data for parents education levels. The data was analyzed using the chi square test. The results showed that there was a relationship between breakfast habits (p = 0.001), parental education level (p = 0.000), and there was no relationship between nutritional status (p = 0.516) and student academic achievement. Based on the research results, it was concluded that there was a significant relationship between breakfast habits and parental education level with the respondents academic achievement and there was no significant relationship between nutritional status with academic achievement in students. Prestasi akademik adalah istilah yang digunakan untuk menunjukan hasil yang didapat seseorang dari proses belajar di dunia pendidikan. Prestasi akademik di Indonesia masih tergolong rendah di mata dunia. Menurut data dari World Best Countries For Education System tahun 2020 Indonesia menempati urutan 70 dengan quality index 46,6 serta opportunity index 42,97 dari 93 negara. Tujuan penelitian ini untuk menganalisis hubungan kebiasaan sarapan, status gizi dan tingkat pendidikan orang tua dengan  prestasi akademik siswa MAN 2 Kabupaten Bogor. Penelitian dilaksanakan pada bulan Mei 2023 di Madrasah Aliyah Negeri 2 Kabupaten Bogor dengan jumlah sampel sebanyak 48 responden yang diambil dengan probability sampling.  Penelitian ini menggunakan metode penelitian kuantitatif dengan desain cross sectional. Pengumpulan data menggunakan kuesioner kebiasaan sarapan untuk kebiasaan sarapan, Z-score untuk status gizi dan data responden untuk tingkat pendidikan orang tua. Analisis data menggunanakan uji chi square. Hasil penelitian menunjukkan terdapat hubungan antara kebiasaan sarapan (p-value = 0,001), tingkat pendidikan orang tua (p-value = 0,000), dan tidak terdapat hubungan status gizi (p-value = 0,516) dengan prestasi akademik siswa. Berdasarkan hasil penelitian disimpulkan bahwa terdapat hubungan yang signifikan antara kebiasaan sarapan dan tingkat pendidikan orang tua dengan prestasi akademik responden dan tidak ada hubungan yang signifikan antara status gizi dengan prestasi akademik pada siswa.